Faktor-Faktor Yang Mempengaruhi Minat Mahasiswa Akuntansi Universitas Bunda Mulia Untuk Mengikuti Brevet Pajak - Sugiyono, Arief; Josephine, Kezia; Tandean, Vivi Adeyani (Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This research aims to determine the influence of tax knowledge motivation, career motivation, and economic motivation on accounting students' interest in taking the tax brevet. This research was conducted in 2022 on students from the Accounting Department at Bunda Mulia University who had completely taken the Taxation course. The research method used is a quantitative method using a questionnaire as a research instrument. The number of samples in this study was 66 people. The results of this research indicate that tax knowledge motivation and career motivation have a positive and significant effect on accounting students' interest in taking the tax brevet, while economic motivation does not have a positive and significant effect on accounting students' interest in taking the tax brevet. The results of this research can also provide input to students regarding the importance of taking a tax brevet as a preparation for entering the world of work.